SUB LETHAL EFFECTS OF ATRAZINE ON HEMATOLOGY, HISTOPATHOLOGY AND BIOCHEMISTRY OF CHIRRUH SNOWTROUT (SCHIZOTHORAX ESOCINUS) - N. Akhtar; M. F. Khan; S. Tabassum (Journal of Animal and Plant Sciences, 2019)
In this study sub lethal effects of atrazine was studied on chirruh snow trout (Schizothorax esocinus), exposed to four different concentrations (1ppm, 2ppm, 3ppm and 4ppm) of atrazine for 96 h. Results of atrazine on fish hematology indicated noteworthy decrease (p≤0.05) in white blood cells (WBCs), RBCs, Hb, HCT, MCH, Monocytes and Lymphocytes concentrations in treated group compared to control group. Substantial increase in MCV, MCHC, platelets and neutrophils was found in all treated group related to control group (p≤0.05). Similarly, histopathological findings of gills of show lamellar disorder, disruption of cartilaginous core, epithelial lifting, blood mobbing, damage to secondary lamellae, fusion of secondary gills lamellae, twisting and shortening of secondary gills lamellae and degeneration and atrophy. Liver presented dissolution of cell membrane, Pyknosis, blood congestion, necrosis, hyperplasia and vacuolations. Intestine show necrosis, hemorrhages, over production of goblet cells in villi, disintegration, fusion and shortening of villi. Muscles have blood congestion at various spots, while brain showed mild necrosis, blood congestion, mild pyknosis and necrosis. It is concluded that atrazine is toxic because it can cause alteration in hematology, biochemistry and histopathology of Schizothorax esocinus.
Keywords: Atrazine; Schizothorax esocinus; Hematology; Biochemistry; Histopathology